Penguatan Pola Asuh Orang Tua bagi Perkembangan Kognitif Anak di Desa Guci Kecamatan Sirampog - Jamiah Jamiah (Jurnal Kependidikan)
The family is the first environment in the education of a child to adapt well according to his age and maturity. In the family, parents have a big role in influencing the development of children's cognitive intelligence. Parenting patterns in early childhood include the provision of physical stimulation, mental stimulation, emotional stimulation, moral stimulation and also social stimulation that will encourage optimal child development. Good parenting will affect the development of children well as well as bad parenting will hinder the development of children. Parenting patterns mean the habits of parents, fathers and mothers in leading, nurturing and guiding children. Nurturing in the sense of keeping by caring for and educating him. Guiding by helping, training, accompanying and so on. The quality and intensity of parenting styles vary in influencing attitudes and directing children's behavior. Therefore, the author will discuss issues related to the relationship between parenting patterns and the development of children's cognitive intelligence, such as the definition of parenting patterns, cognitive intelligence and children. And also discusses the factors that influence the development of children's cognitive intelligence, such as parents' educational background, economy, early marriage, work and environment.The purpose of this study was to determine how big the relationship between parenting patterns and the development of children's intelligence. This research uses descriptive qualitative method. Data collection techniques are observation and interviews. The results showed that parenting greatly influences the development of children's cognitive intelligence in Guci Village, Sirampog District, and good parenting is also influenced by many factors.